Memetakan Intervensi Pemasaran dalam Konsumsi Berkelanjutan, Pencegahan Limbah Makanan, dan Gaya Hidup Tanpa Sampah: Suatu Tinjauan Literatur Sistematis - Nurhayaty, Ety; Siahaan, Febri Sari; Mulina, Rury (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to map the development of research on sustainable consumption and waste prevention in marketing literature, identify forms of marketing interventions that encourage food waste prevention and zero-waste lifestyles, and explain the mechanisms of the relationship between marketing interventions and sustainable consumption behavior. The study uses a systematic literature review design with journal article data sources obtained from the Scopus database and selected according to the PRISMA 2020 guidelines. The selection process resulted in 69 articles being reviewed from an initial 782 records. Data analysis techniques were conducted through descriptive analysis and thematic analysis. The findings indicate a shift in the literature’s focus from general discussions of green purchasing behavior toward a more specific emphasis on food waste reduction and low-waste lifestyles. The identified marketing interventions are no longer limited to green promotions but have expanded to include labeling, packaging design, portion control, visual cues, social media campaigns, digital nudges, brand experiences, apps, and digital platform support. The findings also indicate that the effects of marketing interventions operate indirectly through cognitive, affective, and normative mechanisms, consumer capabilities, segmentation, and system support. The contributions of this research lie in mapping the evolution of the literature, developing a typology of marketing interventions, and creating a conceptual synthesis model of sustainable consumption behavior.